Penerapan Nilai-Nilai Pancasila di Sekolah dalam Mewujudkan Warganegara yang Baik - Jasrudin jasrudin; Dede Sopiandy; Sarmadan Sarmadan (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Pancasila as the foundation of the state and the national ideology embodies specific values that distinguish Indonesia from other countries. The values of belief in God, humanity, unity, democracy, and justice need to be manifested in daily life, especially among students. This study aims to determine the implementation of Pancasila values in fostering good citizenship among students at SD Negeri 1 Lawulo in Kolaka District. The research method used in this study is qualitative descriptive. The research subjects include the school principal, teachers, and students. Data collection techniques in this study include interviews, observations, and documentation. The analysis employed qualitative analysis. The results of this study indicate that: 1) The First Sila of Pancasila is implemented among students through praying before studying according to their respective beliefs, respecting and appreciating friends of different religions; 2) The Second Sila of Pancasila is implemented by promoting honesty during exams, obeying school regulations, refraining from bullying classmates, and assisting classmates who lack pocket money; 3) The Third Sila of Pancasila is implemented by ensuring students do not discriminate based on ethnicity, religion, or skin color, avoiding derogatory remarks towards other ethnicities, and encouraging students to work together in cleaning classrooms and the school environment; 4) The Fourth Sila of Pancasila is implemented by fostering respect for collective decisions and prioritizing common interests, discouraging selfish behavior among students; 5) The Fifth Sila of Pancasila is implemented by promoting fair treatment among peers in assigning tasks for cleaning classrooms and avoiding favoritism towards friends who are in the wrong. The implementation of Pancasila values has contributed to the development of good citizenship, particularly among students at SDN 1 Lawulo in Kolaka District.